Study protocol of a multiphase optimization strategy trial (MOST) for delivery of smoking cessation treatment in lung cancer screening settings - Jamie S. Ostroff; Donna R. Shelley; Lou-Anne Chichester; Jennifer C. King; Yuelin Li; Elizabeth Schofield; Andrew Ciupek; Angela Criswell; Rashmi Acharya; Smita C. Banerjee; Elena B. Elkin; Kathleen Lynch; et al. (Trials, 2022)
Abstract Background There is widespread agreement that the integration of cessation services in lung cancer screening (LCS) is essential for achieving the full benefits of LCS with low-dose computed tomography (LDCT). There is a formidable knowledge gap about how to best design feasible, effective, and scalable cessation services in LCS facilities. A collective of NCI-funded clinical trials addressing this gap is the Smoking Cessation at Lung Examination (SCALE) Collaboration. Methods The Cessation and Screening to Save Lives (CASTL) trial seeks to advance knowledge about the reach, effectiveness, and implementation of tobacco treatment in lung cancer screening. We describe the rationale, design, evaluation plan, and interventions tested in this multiphase optimization strategy trial (MOST). A total of 1152 screening-eligible current smokers are being recruited from 18 LCS sites (n = 64/site) in both academic and community settings across the USA. Participants receive enhanced standard care (cessation advice and referral to the national Quitline) and are randomized to receive additional tobacco treatment components (motivational counseling, nicotine replacement patches/lozenges, message framing). The primary outcome is biochemically validated, abstinence at 6 months follow-up. Secondary outcomes are self-reported smoking abstinence, quit attempts, and smoking reduction at 3 and 6 months. Guided by the Implementation Outcomes Framework (IOF), our evaluation includes measurement of implementation processes (reach, fidelity, acceptability, appropriateness, sustainability, and cost). Conclusion We will identify effective treatment components for delivery by LCS sites. The findings will guide the assembly of an optimized smoking cessation package that achieves superior cessation outcomes. Future trials can examine the strategies for wider implementation of tobacco treatment in LDCT-LCS sites. Trial registration ClinicalTrials.gov NCT03315910